The trial in John Webster's The White Devil: Italy in the reenactment of a Renaissance English drama. (August 2019) - Carpi, Daniela
English playwrights were fascinated by Italy both in a positive and a negative way: they were drawn to Italy as a symbol of culture and refinement, but also as a nest of corruption and bloody conspiracies. Italy had the function of offering a foreign background in which dramatists could safely address their hostility against the English court. This article highlights this fascination with the darker side of Italy in the revision of the trial of Vittoria Accoramboni in John Webster's The White Devil (1612). The story of Vittoria Accoramboni was so famous that many writers appropriated it and re-wrote it centuries after the fact: Stendhal, among others, reproduced the records of the time to offer a historical narration of the events in his Chroniques Italiennes – Vittoria Accoramboni, une oeuvre du domain public (1855). In his turn Webster seized the story, changing some elements such as the setting (he replaced Gubbio with Venice, probably because this town was better known to the audience), fictionalizing the love relationship between Victoria and Duke Brachiano, emphasizing the pandering influence of her brother Flamineo and especially adding his own view of the trial and how it was conducted.